Pathogenesis of local necrosis induced by Naja atra venom: Assessment of the neutralization ability of Taiwanese freeze-dried neurotoxic antivenom in animal models. - Chien-Chun Liu; Yu-Shao Chou; Chun-Yu Chen; Kuei-Lin Liu; Guo-Jen Huang; Jau-Song Yu; Cho-Ju Wu; Geng-Wang Liaw; Cheng-Hsien Hsieh; Chun-Kuei Chen (Public Library of Science (PLoS), 2020)
Naja atra envenomation is one of the most significant clinical snakebite concerns in Taiwan. Taiwanese freeze-dried neurotoxic antivenom (FNAV) is currently used clinically for the treatment of cobra snakebite, and has been shown to limit the mortality of cobra envenomation to less than 1%. However, more than half of victims (60%) require surgery because of local tissue necrosis, a major problem in patients with cobra envenomation. Although the importance of evaluating the neutralizing effect of FNAV on this pathology is recognized, whether FNAV is able to prevent the local necrosis extension induced by N. atra venom has not been investigated in detail. Cytotoxins (CTXs) are considered as the major components of N. atra venom that cause necrosis. In the current study, we isolated CTXs from whole cobra venom and used both whole venom and purified CTXs to develop animal models for assessing the neutralization potential of FNAV against venom necrotizing activity. Local necrotic lesions were successfully produced in mice using CTXs in place of whole N. atra venom. FNAV was able to rescue mice from a subcutaneously injected lethal dose of cobra venom; however, it was unable to prevent CTX-induced dermo-necrosis. Furthermore, using the minimal necrosis dose (MND) of CTXs and venom proteome data, we found a dose of whole N. atra venom suitable for FNAV and developed a workable protocol for inducing local necrosis in rodent models that successfully imitated the clinical circumstance of cobra envenoming. This information provides a more comprehensive understanding of the pathophysiology of N. atra envenomation, and serves as a guide for improving current antivenom strategies and advancing clinical snakebite management in Taiwan.